Strategy for Identifying Repurposed Drugs for the Treatment of Cerebral Cavernous Malformation. Issue 3 (20th January 2015) - Gibson, Christopher C.; Zhu, Weiquan; Davis, Chadwick T.; Bowman-Kirigin, Jay A.; Chan, Aubrey C.; Ling, Jing; Walker, Ashley E.; Goitre, Luca; Delle Monache, Simona; Retta, Saverio Francesco; Shiu, Yan-Ting E.; Grossmann, Allie H.; et al.
<x xml:space="preserve">Abstract</x> Background— Cerebral cavernous malformation (CCM) is a hemorrhagic stroke disease affecting up to 0.5% of North Americans that has no approved nonsurgical treatment. A subset of patients have a hereditary form of the disease due primarily to loss-of-function mutations in KRIT1, CCM2, or PDCD10. We sought to identify known drugs that could be repurposed to treat CCM. Methods and Results— We developed an unbiased screening platform based on both cellular and animal models of loss of function of CCM2. Our discovery strategy consisted of 4 steps: an automated immunofluorescence and machine-learning–based primary screen of structural phenotypes in human endothelial cells deficient in CCM2, a secondary screen of functional changes in endothelial stability in these same cells, a rapid in vivo tertiary screen of dermal microvascular leak in mice lacking endothelial Ccm2, and finally a quaternary screen of CCM lesion burden in these same mice. We screened 2100 known drugs and bioactive compounds and identified 2 candidates, cholecalciferol (vitamin D3) and tempol (a scavenger of superoxide), for further study. Each drug decreased lesion burden in a mouse model of CCM vascular disease by ≈50%. Conclusions— By identifying known drugs as potential therapeutics for CCM, we have decreased the time, cost, and risk of bringing treatments to patients. Each drug also prompts additional exploration of biomarkers of CCM disease. We further suggest that the structure-function screening platform presented here may be adapted and scaled to facilitate drug discovery for diverse loss-of-function genetic vascular disease.